Genetic analyses of lumbosacral transitional vertebra and hip dysplasia in nine dog breeds in Norway - Jon Andre Berg; Bente Kristin Sævik; Cathrine Trangerud; Per Madsen; Frode Lingaas (Acta Veterinaria Scandinavica)
Abstract Background A lumbosacral transitional vertebra (LTV) is a congenital anomaly with reported prevalences ranging from 0 to 67% in different dog breeds, implying possible genetic differences. LTV has been associated with canine hip dysplasia (CHD) and degenerative lumbosacral stenosis (DLSS). Genetic parameters, including heritability estimates, are important for understanding the genetic influence on specific traits and for evaluating the effectiveness of possible genetic selection in reducing the prevalence of disorders. This study aimed to determine the heritability of LTV in nine dog breeds in Norway and estimate the genetic correlation with CHD. Results The heritability estimates for LTV across the nine breeds ranged from low to moderate (0.056–0.314), while the heritability estimates for CHD were moderate to high (0.254–0.580). The estimates of genetic correlations between the two traits were mostly non-significant and varied strongly among breeds in size and direction. Conclusions This study indicated that genetic factors influence LTV in several breeds and that there is a potential to reduce the prevalence by genetic selection, even if the heritability estimates of LTV ranged from low to moderate. The heritability estimates of CHD were within the range reported earlier, ranging from moderate to high. There was no general indication of a genetic correlation between LTV and CHD across breeds.